2011
DOI: 10.1542/peds.2011-0245
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Medical Comorbidity and Quality of Life Outcomes in Childhood-Onset Epilepsy

Abstract: Psychiatric comorbidities are strongly associated with long-term HRQoL in childhood-onset epilepsy, which suggests that comprehensive epilepsy care must include screening and treatment for these conditions, even if seizures remit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(152 citation statements)
references
References 76 publications
10
137
1
4
Order By: Relevance
“…Migraineurs affected by focal epilepsies had a risk for cryptogenic epilepsy that was three times higher than that for idiopathic epilepsy. Recently, adolescents with any headache type were reported (Lateef et al 2012) to have significantly higher rates of epilepsy, as previously confirmed by Baca et al (2011), who found the comorbidity of migraine and epilepsy in 15 % of the children they studied. Interestingly, Colombo et al (2011), whose data confirmed previous findings (Sasmaz et al 2004) showing that almost 36 % of parents of children with headache are unaware of the headache, stressed that pediatric headache is still under-diagnosed and is not adequately considered as a health problem either by the medical community or in social settings: on the one hand, this indicates the extent to which headache is underestimated, on the other, it confirms that the clinical picture in co-morbid cases is dominated by the diagnosis of epilepsy.…”
Section: Epidemiological Issues: Beyond the Controversial Evidencesupporting
confidence: 62%
“…Migraineurs affected by focal epilepsies had a risk for cryptogenic epilepsy that was three times higher than that for idiopathic epilepsy. Recently, adolescents with any headache type were reported (Lateef et al 2012) to have significantly higher rates of epilepsy, as previously confirmed by Baca et al (2011), who found the comorbidity of migraine and epilepsy in 15 % of the children they studied. Interestingly, Colombo et al (2011), whose data confirmed previous findings (Sasmaz et al 2004) showing that almost 36 % of parents of children with headache are unaware of the headache, stressed that pediatric headache is still under-diagnosed and is not adequately considered as a health problem either by the medical community or in social settings: on the one hand, this indicates the extent to which headache is underestimated, on the other, it confirms that the clinical picture in co-morbid cases is dominated by the diagnosis of epilepsy.…”
Section: Epidemiological Issues: Beyond the Controversial Evidencesupporting
confidence: 62%
“…The high proportions of medical disorders were a more surprising finding. Some of the specific medical diagnoses, such as asthma, have been investigated in other studies, 22,23 and found to be increased in CWE. However, few previous studies have assessed a broad range of medical disorders in CWE, so we will focus on this in the remainder of the discussion.…”
Section: Discussionmentioning
confidence: 93%
“…12 -21 Knowledge about other medical comorbidities is limited, and only a couple of studies have investigated this in children specifically. 22,23 Most studies of medical comorbidities have included only adults or subjects of all ages and primarily reported findings in adults. 24 -34 Some studies have focused on specific diagnoses rather than an extensive range.…”
mentioning
confidence: 99%
“…19,20 Psychiatric disorders were analyzed in groups for externalizing disorders (attention-deficit/hyperactivity, conduct, and oppositional-defiant) and internalizing disorders (depression, anxiety, obsessivecompulsive, and bipolar). Learning problems, including developmental delay, language problems, and dyslexia, were also grouped into a single dichotomous variable.…”
Section: Psychiatric and Learning Problemsmentioning
confidence: 99%